2017
DOI: 10.1007/s10993-017-9436-4
|View full text |Cite
|
Sign up to set email alerts
|

Engineering commodifiable workers: language, migration and the governmentality of the self

Abstract: This article examines the strategies and forms of expertise on language and communication mobilized to engineer commodifiable migrant workers. Drawing on an ethnographic account of counselling practices in a state-run Italian job guidance centre for newly arrived migrants, I examine the calculations, tactics, and forms of expertise on language and communication mobilised by job counsellors. Here, I illustrate how these tactics regulate, or ''police'', migrants' communicational conduct and promote their sociali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 24 publications
1
23
0
3
Order By: Relevance
“…We have discussed, how individuals who ensure that this economy continues to grow at a spectacular pace make sense of their part in a neoliberal industry that is characterized by uncertainty, flexibility and a hierarchical work order but at the same time rewards selfrealization and self-improvement within the structures and constraints of the linguistic market. Similar to what has been demonstrated elsewhere in different contexts of language work within neoliberal economies (Cameron 2000;Del Percio 2018;Duchêne 2011;Park 2016;Rahman 2009), aspiring for a career in the medical tourism industry requires continuous investments and self-work, with language as the central work tool and product. As we have demonstrated along the trajectories of three aspiring healthcare entrepreneurs, language skills indeed became commodities and as such, central in attempts to access potentially lucrative foreign healthcare markets.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…We have discussed, how individuals who ensure that this economy continues to grow at a spectacular pace make sense of their part in a neoliberal industry that is characterized by uncertainty, flexibility and a hierarchical work order but at the same time rewards selfrealization and self-improvement within the structures and constraints of the linguistic market. Similar to what has been demonstrated elsewhere in different contexts of language work within neoliberal economies (Cameron 2000;Del Percio 2018;Duchêne 2011;Park 2016;Rahman 2009), aspiring for a career in the medical tourism industry requires continuous investments and self-work, with language as the central work tool and product. As we have demonstrated along the trajectories of three aspiring healthcare entrepreneurs, language skills indeed became commodities and as such, central in attempts to access potentially lucrative foreign healthcare markets.…”
Section: Discussionsupporting
confidence: 53%
“…In line with neoliberal ideology (Harvey 2005;Gershon 2011), current and future healthcare markets must be read, anticipated and engaged with to profit from a rapidly growing yet largely unregulated service industry. Further, in order to stand out it is up to the individual speaker to strategically invest in one's own multilingualism, professional knowledge, and communicative conduct (Del Percio 2018;Urciuoli 2008;Park 2016), adhering to an imperative of constant self-improvement.…”
Section: Introductionmentioning
confidence: 99%
“…A critical sociolinguistics of governmentality has addressed how neoliberal governmentality operates through the processes of subjectification and self‐governance in particular (e.g. Allan, 2013; Barakos, 2016; Del Percio, 2018; Dlaske, 2016; Martín Rojo, 2019). This article illustrated how a nexus of different governmentality technologies and bodies of knowledge are employed in the mine’s governmentality apparatus that combines the neoliberal technology of responsibilization with the disciplinary strategies of surveillance, supervision, and regulations.…”
Section: Resultsmentioning
confidence: 99%
“…Neoliberal governmentality is constructed, strengthened, and disseminated via discourse by means of daily institutional practices (Martín Rojo & Del Percio, 2019: 2). Hence, previous sociolinguistic research adopting a governmentality framework has primarily focused on analyzing how language has been used as a medium for neoliberal governmentality in the management, guidance, and training of individuals, such as language learners (Flubacher & Del Percio, 2017; Martín Rojo, 2019), workers (Barakos, 2016; Dlaske, 2016), and unemployed immigrants (Allan, 2013; Del Percio, 2018). These studies have shown how individuals are governed through ‘technologies of the self’, by making them internalize neoliberal requirements such as responsibility, flexibility, and employability, and, seemingly voluntarily, regulate their behavior accordingly.…”
Section: Applying the Concept Of Apparatus To The Study Of Governmentmentioning
confidence: 99%
“…The Language Policy special issue edited by Muth and Del Percio (), for instance, brings together studies that explore the specific institutional and discursive conditions that attribute economic value to different varieties of language in local context. These studies show that management of multilingualism for economic purposes is shaped not only by shifts in market conditions (Muth ) but also by multiple constraints, such as local circulation of state‐based ideologies of commodification (Brennan ), transnational identity construction of a community (Bolander ), older hierarchies of value attributed to language (Van Hoof ), as well as resistance toward this logic of commodification (Del Percio ). Similarly, Flubacher, Duchêne, and Coray's () ethnography of public employment service in Fribourg raises issues with how the bureaucracy's vague conceptualizations of language obscure the complexity of the correlation between language learning and employment, thereby leading to rationalizations of class, race, and gender‐based inequalities.…”
Section: Shifts In the Political Economymentioning
confidence: 99%